Situating smartphones and social media usage in learning activities among university students / Munawwarah Mohd Azmir and Ahlam Abdul Aziz. - Mohd Azmir, Munawwarah; Abdul Aziz, Ahlam (Faculty of Communication and Media Studies, Universiti Teknologi MARA, 2018)
Smartphones ownership amongst the general customer, professionals and even students has grown exponentially. The latent features of smartphones in education somehow support learning activities. This paper aims to situate the evolving communication technology in higher education context. Smartphones like table computers and other mobile devices are evolved pieces of technology that have the potential to support student learning in the classroom. University students can use smartphones to record a lecture, search for definitions, or send notes to absent students, as well as use the medium to collaborate with other students electronically to complete homework assignments (Cheung, 2009). Nevertheless, smartphones also enable the use of social media or social networks by university students that it has somehow became significant to their academic life. Students used social media for a variety of reasons which comprise of study and entertainment purposes as those sites provide a broad range of data which can be retrieved easily and fast (Raut & Patil, 2016). With the increase of social media use by students over past years, there are various impacts, both positive and negative specifically to the students and society in general can be examined.